Case report: Aromatic L-amino acid decarboxylase deficiency in three patient cases from the Kingdom of Saudi Arabia - Abukhaled, Musaad; Alrakaf, Laila; Aldhalaan, Hesham; Al Yamani, Suad (Frontiers in Pediatrics, 2023)
Aromatic L-amino acid decarboxylase (AADC) deficiency is an ultra-rare and often severe neurometabolic disorder resulting from variants in the dopa decarboxylase (DDC) gene. A timely diagnosis is critical to prevent secondary complications, promote development, and optimize outcomes from future innovative treatment options, such as gene therapy. This article describes three patients with AADC deficiency managed in the Kingdom of Saudi Arabia (KSA). All three patients had homozygous variants within the DDC gene, including one novel gene variant (c.245G>A, p.Arg82Glu), and presented with symptoms from birth. In all cases, a diagnostic delay was observed owing to non-specific signs and symptoms, a lack of disease awareness among primary care physicians, and delays associated with outsourcing of genetic tests. All three patients were managed by a multidisciplinary team at a specialist tertiary center. Clinical outcomes for all three cases were poor, with one patient passing away at 3 years of age and the other two patients continuing to experience substantial disability and poor quality of life. There is an urgent need to raise awareness and improve diagnostic testing for rare diseases such as AADC deficiency in the KSA in order to improve outcomes, particularly as innovative disease-targeting therapies become available.